ANALISIS MELODI GAMBUS LAGU ANAK AYAM PADA MUSIK IRINGAN TARI JEPIN SENGARONG KABUPATEN SANGGAU - Renidianti Renidianti; Aloysius Mering; Chiristianly Yery Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this research was to analyze gambus melody of Anak Ayam song on accompaniment music of Jepin Senggarong dance that focused on three special purpose there are 1) The description of gambus melody structure of Anak Ayam, 2) The description of gambus melody form of Anak Ayam song, and 3) The description of gambus melody contour of Anak Ayam song. The form of this research was descriptive qualitative with a musicology analysis approach. The research data obtained from data collected technique with interview, observation, and documentation with interviewers, wich ware Abang Saka, Muhammad Riva’i Napis, and Sunaryo as the art practitioner in Sanggau Regency. The data validity in this researc was tested with triangulation data. Based on the analysis, the gambus melody of Anak Ayam has one form of music that consist of mawal melody and the main melody of Anak Ayam song. The Gambus melody of Anak Ayam song played with harmonic minor scale that created pendulous contour. There were some processed motive and figure on the Gambus melody of Anak Ayam song wich are literal repetition, up sequence, down sequence, and interval enlargement. Keywords:  Analysis, Anak Ayam Song, Gambus Melody, Jepin Sengarong Dance